PENGARUH LOCUS OF CONTROL DAN KOMPLEKSITAS TUGAS TERHADAP KINERJA PEGAWAI: (Studi pada Kantor Inspektorat Kota Pasuruan) - Yuyun Masruroh; Eva Mufidah; Vita Fibriyani (Media Mahardhika, 2020)
The Inspectorate of Pasuruan City in carrying out its function required good performance management to support the implementation of development in Pasuruan area. Many factors affect employee performance such as locus of control and task complexity. This research aims to determine the influence of locus of control and the complexity of the task to the performance of employees (study at the Office of Inspectorate Pasuruan City). The samples used were the entire population of the staff in Pasuruan's Inspectorate of 33 employees using census techniques. Data collection techniques using questionnaires. The data analysis used in this study is a double linear regression analysis. Based on the results of the study obtained locus of control and the complexity of the task simultaneously affect the performance of employees evidenced by the value of Fcount 18.592. A partial locus of control affects the performance of employees evidenced by the value of Thitung 3.306 and the complexity of the task affects the performance of employees evidenced by the value of Thitung 2.901. Its adjustable R Square number indicates that 52.4% of employee performance variables can be explained by the locus of control variables and task complexity in the regression equation, while the remainder of 47.6% is described by other variables outside the variables used in this study. The better the locus of control and the complexity of the task then the better the employee performance.